Вы находитесь на странице: 1из 5

# Page 1 of 5

## Properties of Complex Numbers Proof:

Like Real numbers, properties of addition and Let z 1=a+bi , z 2=c +di∧z 3=e+ fi
multiplication also hold in complex numbers.
L.H.S. = z 1+ ( z2 + z 3 )

## A – 1: Addition is commutative i.e. for any two = ( a+bi ) + [ ( c + di ) + ( e+ fi ) ]

complex numbers z 1 , z 2 , we have
= ( a+bi ) +[ ( c+ e ) + ( d+ f ) i]
z 1+ z 2=z 2 + z 1
= a+ ( c+ e ) + [ b+ ( d +f ) ] i
Proof: Let z 1=a+bi , z 2=c +di
= ( a+ c ) + e+ [ ( b+ d ) +f ] i [By Associatively in
L.H.S. = z 1+ z 2
R]
= ( a+bi ) + ( c+ di) = ( a+ c ) + e+ ( b+ d ) i+ fi
= ( a+ c ) + ( b+d ) i = ( a+ c ) + ( b+d ) i+ e+ fi
= ( c +a ) + ( d+ b ) i = [ ( a+bi ) + ( c + di) ]+ ( e+ fi )
a , b , c , d ∈ R and Commutative law holds in R]
¿ = ( z 1+ z2 ) + z 3
= c +di+a+ bi
= R.H.S.
= z 2+ z 1 Example 1.3.2
= R.H.S. If z 1=1+2i , z2 =−2+3 i∧z 3=−3−5 i
Example 1.3.1
Then z 1+ ( z2 +z 3 )=( z1 + z 2 ) + z 3
If z 1=1+3 i, z 2=3−5 i then
Solution:
z 1+ z 2=z 2 + z 1 .
L.H.S. = z 1+ ( z2 + z 3 )
Solution:

## = ( 1+3 ) + ( 3−5 ) i = ( 1+2i ) + (−5−2 i )

= 4−2 i = ( 1−5 ) + ( 2−2 ) i
R.H.S. = z 2+ z 1 = −4+ 0.i

= ( 3−5 i ) + ( 1+3 i ) = −4

## = 3+1−5 i+3 i R.H.S. = ( z 1+ z2 ) + z 3

= 4−2 i = [ ( 1+2i ) + (−2+3 i ) ]+ (−3−5i )
Hence L.H.S. = R.H.S.
= [ ( 1−2 ) + ( 2+3 ) i ] + (−3−5 i )
A – 2: Addition is Associative i.e. for any three complex
numbers z 1 , z 2 , z 3 we have;
= (−1+5 i ) + (−3−5 i )
= (−1−3 ) + ( 5−5 ) i
z 1+ ( z2 +z 3 )=( z1 + z 2 ) + z 3
Page 2 of 5

## = −4+ 0.i R.H.S. = z2 . z1

= −4 = (−1+2 i ) ( 2−3 i )
Hence L.H.S. = R.H.S.
= (−2+ 3i+ 4 i−6 i2 )
Properties of Multiplication
= −2+7 i+6
M – 1: Multiplication is Commutative i.e. for any two
complex numbers z 1 , z 2 we have
= −2+6 +7 i
z 1 . z 2=z 2 . z 1 = 4 +7 i
Proof: = L.H.S.

## For any three complex numbers z 1 , z 2∧z 3 we

= ( a+bi ) ( c +di )
have; z 1 ( z 2 . z 3 )=( z1 . z2 ) z 3
2
= ( ac +adi+bci+bd i )
Proof:
= ( ac−bd ) + ( ad+ bc ) i (As
2
Let z 1=a+bi , z 2=c +di , z 3=e+ fi
i =−1 ¿
L.H.S. = z1 ( z2 . z3 )
R.H.S. = z2 . z1

= ( c +di ) ( a+bi )
= ( a+bi ) [ ( c +di ) ( e+ fi ) ]

## = L.H.S. = a ( ce−df )+ a ( cf +de ) i+ib ( ce−df )

Hence Proved 2
+b i ( cf + de )
Example 1.3.3
a ( cf + de )
=
If z 1=2−3 i , z 2=−1+2 i then a ( ce−df )−b ( cf + de ) +i ¿
z 1 . z 2=z 2 . z 1
+b ( ce−df ) ¿
Solution:
R.H.S. = ( z1 . z2 ) z3
L.H.S. = z1 . z2
= [ ( a+bi ) . ( c+ di ) ] ( e+ fi )
= ( 2−3 i ) (−1+2 i )
2
= [ a ( c +di ) +bi ( c+ di ) ] ( e + fi )
= −2+ 4 i+3 i−6 i
= [ ac +adi+bci+bd i2 ] ( e+ fi )
= −2+7 i+6
= −2+6 +7 i
= [ ( ac−bd ) +( ad+bc ) i ] ( e + fi )
=
= 4 +7 i
( ac−bd ) e+ if ( ac−bd ) +ie ( ad +bc ) +i 2 f ( ad+ bc )
Page 3 of 5

## = Q.1: If z 1=1+i, z 2=2+i , then verify that

e ( ac−bd )−f ( ad+ bc )+i ( acf −bdf +ade+ bce )
( i ) z 1 + z 2=z 2+z 1 ( ii ) z 1 . z 2=z 2 . z 1
=
ace−bde−adf −bcf +i ( acf +ade +bce−bdf ) Name which property is satisfied in each case.

= Solution:

## a ( ce−df )−b ( de +cf ) +i [ a ( cf + de ) +b ( ce−df ) ] (i) L.H.S. = z 1+ z 2

= L.H.S. = ( 1+i )+ ( 2+ i )
Hence z 1 ( z 2 . z 3 )=( z1 . z2 ) z 3 = 1+2+i+i
Example 1.3.4: = 3+2 i
If z 1=1−i , z 2=−1+2 i, z 3=2−3i then R.H.S. = z 2+ z 1
z 1 ( z 2 . z 3 )=( z1 . z2 ) z 3 = ( 2+i )+ ( 1+ i )
Solution: = 2+1+i+i
L.H.S. = z1 ( z2 . z3 ) = 3+2 i

## = ( 1−i ) [ (−1+2 i )( 2−3i ) ] Hence z 1+ z 2=z 2 + z 1

Commutative property w.r.t addition is satisfied.
= ( 1−i ) (−2+3 i+4 i−6 i 2 )
(ii) L.H.S. = z1 . z2
= ( 1−i ) (−2+7 i+6 ) [ Asi 2=−1 ]
= ( 1+i )( 2+i )
= ( 1−i ) (4+7 i)
2
= 2+i+ 2i +i 2
= 4 +7 i−4 i−7 i
= 2+3 i−1 [ As i 2=−1 ]
= 4 +3 i+7 [ As i =−1 ] 2

= 2−1+3 i
= 11+3 i
= 1+3 i
R.H.S. = ( z1 . z2 ) z3
R.H.S. = z2 . z1
= [ ( 1−i ) (−1+2 i ) ] ( 2−3i )
= ( 2+i )( 1+i )
2
= (−1+ 2i+i−2 i ) ( 2−3i )
= 2+2i+i+i 2
= (−1+3 i+2 ) ( 2−3 i ) [ As i 2=−1 ]
= 2+3 i−1 [ As i 2=−1 ]
= ( 1+3 i ) ( 2−3 i )
= 2−1+3 i
2
= 2−3 i+ 6 i−9 i = 1+3 i
= 2+3 i+ 9 [ As i 2=−1 ] Hence z 1 . z 2=z 2 . z 1
= 11+3 i Commutative property w.r.t. Multiplication is satisfied.

## Hence z 1 ( z 2 . z 3 )=( z1 . z2 ) z 3 Q.2: If z 1=−1−i , z 2=3+2 i , z 3=−2+3 i

Exercise 1.2 Then verify that:
Page 4 of 5

## (i) z 1+ ( z2 + z 3 )=( z1 + z 2 ) + z 3 = (−3−5 i+ 2 )(−2+3 i )

(ii) z 1 ( z 2 . z 3 )=( z1 . z2 ) z 3
= (−1−5 i )(−2+3 i )
Name which property is satisfied in each case.
= 2−3 i+10 i−15 i2
Solution:
= 2+7 i+15
(i) L.H.S. = z 1+ ( z2 + z 3 )
= 2+15+7 i
=
(−1−i )+ [ ( 3+2i ) + (−2+3 i ) ] = 17+7 i

## = −1+1−i+5 i Note: According to the commutative property for

= 0+ 4 i multiplication iy= yi . Hence we can write
= 4i z=x +iy instead of z=x + yi.

## A complex number a+bi is called the additive

=
identity for the set of complex numbers if for any
[ (−1−i )+ ( 3+2i ) ] +(−2+3 i) complex number x+ yi , we have;
= (−1+3−i+2i ) + (−2+3 i ) ( x+ yi )+ ( a+bi )=( a+bi ) + ( x+ yi )=x+ yi this
= ( 2+i )+ (−2+3 i ) is possible only if a=0∧b=0 i.e.

= 4i And;

## Hence z 1+ ( z2 +z 3 )=( z1 + z 2 ) + z 3 ( 0+0 i ) + ( x+ yi )=( 0+ x ) + ( 0+ y ) i=x + yi

Definition 1.3.2:
Associative property w.r.t. addition is satisfied.
A complex number a+bi is called the
(ii) L.H.S. = z1 ( z2 . z3 )
multiplicative identity for the set of complex numbers
= (−1−i)[ ( 3+2 i ) . (−2+3 i ) ] if for any complex number x+ iy , we have;
= (−1−i ) (−6+ 9i−4 i+6 i 2 )
= (−1−i )(−6+5 i−6 ) ( x+ yi )( a+ bi )=( a+ bi )( x + yi )=x + yi .
= (−1−i )(−12+5 i ) This is only possible if a=1∧b=0 , i.e.
2
= 12−5 i+ 12i−5 i
= 12+7 i+5 a+bi=1+ 0 i because;
= 12+5+7 i
= 17+7 i
R.H.S. = ( z1 . z2 ) z3
= [ (−1−i )( 3+2 i ) ] (−2+3 i )
=
(−3−2 i−3 i−2 i 2) (−2+3 i )
Page 5 of 5